Assessment Of Dental Caries And Oral Health Care In Children And The Impact Of School On Them (Cross-sectional study) (Latakia University Journal -Medical Sciences Series, 2025)
Introduction: Dental caries remains the most prevalent disease among humans and is particularly common in children aged 5 to 17 years, according to World Health Organization statistics from 2022. Schools and communities play a significant role in public and dental health by reducing the spread of diseases through awareness and timely management.Objective of the Study: To assess the impact of schools (public and private) on the prevalence of dental caries and caries risk assessment, frequency of tooth brushing, and number of dental visits.Materials and Methods: This cross-sectional study included 370 children from public and private schools in the city of Latakia, aged between 6 and 10 years.Their teeth were examined to evaluate the prevalence of caries and caries risk assessment using the DMFT/dmft index. Additionally, a questionnaire was used to assess oral healthcare practices.Results: There were no statistically significant differences in the prevalence of dental caries, caries risk assessment, frequency of tooth brushing, or number of visits to the dentist between public and private schools.Conclusion: The current study found that whether a child attends a private or public school does not affect the prevalence of dental caries, caries risk assessment, oral health care practices.
Keywords: Dental caries, caries risk assessment, DMFT/dmft index, tooth brushing, dental visits, school.